Two Crises Separated by a Decade: Political Economy of Trade Strategy and Reserves Accumulation in East Asia. Issue 2 (September 2021) - Nag, Biswajit; Ray, Partha
This article seeks to explore the relationship between the global financial crisis (2007–2009) and the East Asian crisis (1997–1999) via the contribution of select East Asian countries, which led to the formation of the 'global imbalance', that is, experience of substantial and consistent current account surplus. Taking a cue from Bernanke's 'savings glut' hypothesis, which has held 'global imbalance' to be a factor behind the global financial crisis, specifically, the article argues that in these countries, the nature of current account balance has undergone a sea change since the end of the 1990s. They also accumulated a substantial amount of foreign exchange reserves since then along with a major shift of trade regime and consequent trade surplus in all these countries. The article conjectures that the mishandling of the rescue package by International Monetary Fund could have induced them to go aggressively for accumulation of forex reserves. Thus, the two crises separated by a decade and in different continents are, indeed, linked through providing an incentive for brewing up of global imbalance via an activist trade policy in select East Asian countries. Seen in this context and from this standpoint, the two crises, indeed, appear to be close siblings! JEL Codes: F41, F62, O53